2015 48th Hawaii International Conference on System Sciences 2015
DOI: 10.1109/hicss.2015.12
|View full text |Cite
|
Sign up to set email alerts
|

A Framework to Inform Design of Learning Objects for Teaching Written Portuguese (2nd Language) to Deaf Children via Sign Language (1st Language)

Abstract: Bilingualism is the philosophy of choice for deaf education and literacy: deaf children should learn Sign Language for intellectual development, and the written form of the oral language. Unfortunately, educators are still influenced by the clinical view of deafness as a deficiency to be removed, and that view influences their pedagogical praxis that lack proper pedagogical tools. Additionally, there has been a political setback: special schools for the deaf in Brazil are being closed. Mainstream schools are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…Prelingually deaf children face communication challenges due to the late acquisition of a first language at home, as 90% of these children have hearing parents [4] [5] who do not know Sign Language (SL). SL is seen as the mother tongue of deaf community [6] [7] and many countries legally recognize it as such [7] [8].…”
Section: Education Of Deaf Childrenmentioning
confidence: 99%
“…Prelingually deaf children face communication challenges due to the late acquisition of a first language at home, as 90% of these children have hearing parents [4] [5] who do not know Sign Language (SL). SL is seen as the mother tongue of deaf community [6] [7] and many countries legally recognize it as such [7] [8].…”
Section: Education Of Deaf Childrenmentioning
confidence: 99%
“…A moré narrowéd approach was dévélopéd by Guimara és ét al. [21] to inform désign of léarning objécts for téaching writtén Portuguésé to déaf childrén. This framéwork is spécifically créatéd for a particular léarning goal (writing) and disability (déafnéss).…”
Section: Designing For People With Disabilitiesmentioning
confidence: 99%
“…One of the main reasons Deaf people do not finish higher education is due to poor literacy skills [29]. The development of reading and writing skills is a challenge for most Deaf children especially because 90% of these children are born from non-Deaf parents [30] [21]; this could become in the first issue these children face (communication with parents) and it may derive in a late acquisition of a first language (L1) which should be a Sign Language (SL) that parents probably do not use. Learning a first language during the first five years is critical in order to acquire a second language (L2) in a written form (for instance, English or Spanish) [31] which will give them the opportunity to communicate with hearing people who do not know a SL.…”
Section: Literacy In Deafmentioning
confidence: 99%
“…al, 1984;Volterra & Erting, 1984). Guimarães et al (2015) found that the narrative of the educators was that of the "hearing" Deaf: "The Deaf who has speaking conditions should work on it because they are going to live with hearing people and their alphabetization will be easier". Others were adamant about the Deaf's ability to learn: "We can affirm that the Deaf student will never achieve interpretation and production of writing in an integral manner".…”
Section: Current State Of Affairsmentioning
confidence: 99%